Application of The Discovery Learning Model Using Tiktok Media in Lecture Text Material - Dian Puspita sari; Nazurty; Nurfadilah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
The purpose of this research is to answer how the application of TikTok as an ICT-based learning media on lecture text material using the discovery learning method. This research is a qualitative research in descriptive study. The data sources of this research were obtained from interviews, observations, and documentation. The technique of taking informants is random sampling. Data collection techniques are triangulated. Data analysis techniques are carried out with three stages, namely reduction, data presentation, and conclusion drawing. Based on the results of the study, it can be concluded that the application of the TikTok application can be done by making video lessons of lecture material and uploading them in general. Thus students can listen to lecture text material through their respective TikTok and can repeat the material anytime and anywhere.